2022
DOI: 10.1177/02734753211070561
|View full text |Cite
|
Sign up to set email alerts
|

Don’t Waste a Crisis: COVID-19 and Marketing Students’ Self-Regulated Learning in the Online Environment

Abstract: This research examines the extent to which a crisis situation, such as the COVID-19 pandemic, affects marketing students’ self-regulated learning (SRL) and grade expectations. Data were collected from 841 undergraduate marketing students and analyzed using the Hayes process macro to test the proposed framework. The results show direct and significant effects of SRL and its substrategies (goal setting, environmental structuring, and time management) on students’ grade expectations. However, help-seeking and sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 98 publications
(142 reference statements)
0
3
0
Order By: Relevance
“…The Covid-19 pandemic also directly affects self-regulated learning in an online learning environment. Research by Meshram (2022) investigates how the COVID-19 pandemic affected marketing students' self-regulated learning and grade expectations. The Hayes process macro was used to test the proposed framework on 841 undergraduate marketing students, and the findings indicate that SRL and its sub strategies have a direct and significant impact on students' grade expectations.…”
Section: Past Studies Of Self-regulated Learningmentioning
confidence: 99%
“…The Covid-19 pandemic also directly affects self-regulated learning in an online learning environment. Research by Meshram (2022) investigates how the COVID-19 pandemic affected marketing students' self-regulated learning and grade expectations. The Hayes process macro was used to test the proposed framework on 841 undergraduate marketing students, and the findings indicate that SRL and its sub strategies have a direct and significant impact on students' grade expectations.…”
Section: Past Studies Of Self-regulated Learningmentioning
confidence: 99%
“…From a social cognitive theory perspective, help-seeking in academic contexts involves students' agentic and self-regulated gathering of information from a variety of sources that can be used to help them achieve their educational goals (e.g., Meshram et al, 2022;Zimmerman, 2000). Drawing on social supports such as those discussed above, help-seeking can facilitate student success, but as Harvey et al (2006) observed, "students who most need the support are not always those who make use of it" (p. 4).…”
Section: Help-seekingmentioning
confidence: 99%
“…help-avoidance "Instances when students know that they need help but do not seek it" (Ryan et al, 2001, p. 94). help-seeking Students' agentic and self-regulated gathering of information from a variety of sources that can be used to help them achieve their educational goals (e.g., Meshram et al, 2022;Zimmerman, 2000). imposter phenomenon/ syndrome In the academic environment, "intellectual self-doubt" (Schubert & Bowker, 2017, p. 749) like feelings/beliefs that one should not be (does not deserve to be) where they are, or that their success is due to luck or chance instead of their own abilities.…”
Section: Affordances and Constraintsmentioning
confidence: 99%